"We ought to obey God rather then men": John Rogers's millenarian hermeneutics and legal reform in 1653. Issue 3 (4th May 2022) - Giugni, Astrid Adele
ABSTRACT: This article analyses two polemical works by the Fifth Monarchist John Rogers to argue that Interregnum Millenarian Scriptural hermeneutics cogently draws on Scholastic as well as Reformed authorities. This article traces how in the years of 1652–3, during which England transitions from the rule of the Rump Parliament to the Nominated Assembly, Rogers adapts the questions on voluntary action and human law from Thomas Aquinas's Summa Theologiæ to extend his defence of Congregationalism to an argument for rule by the Saints. Fifth Monarchists, by labelling all laws and forms of government that were not strictly Biblical as anti-Christian, claim to bypass the problem of how to reconcile human custom with Scriptural law. Ironically, Rogers's argument for the applicability of Deuteronomic law to all nations and at all times draws on Thomistic Aristotelianism to develops its hermeneutical strategies.